Cerebral Vasospasm – A serious obstacle in a successful aneurysm surgery - Florin Stefanescu (Romanian Neurosurgery, 2013)
Background: Cerebral vasospasm that occurs after subarachnoid hemorrhage (SAH) can be an important cause of mortality and morbidity for patients successfully operated for a cerebral aneurysm. Methods: Five cases of prompt diagnostic and surgical treatment of a cerebral aneurysm, with important SAH on cerebral computed tomography (CT) at onset, are presented. All patients were admitted in a poor neurological state and developed severe vasospasm. Both, the correct clipping of the aneurysm and the cerebral vasospasm were angiographic demonstrated in all cases. Two patients showed complete obliteration of one carotid artery. Results: Postoperatory, four of the patients were treated with intrathecally administered nimodipine (10mg/50ml). In three cases, the procedure caused the reverse of the vasospasm and clinical improvement of the patients. Their clinical outcomes were very good and were discharged with minimal neurological deficits. In one case, repeated intraarterial administration of nimodipine, showed no reduction of the vasospasm, and no improvement of patient’s clinical status. The patient was conscious, but presented focal neurological deficits (hemiplegia and aphasia). One patient did not benefit from this treatment and had a poor clinical outcome, remaining in a vegetative state. Conclusions: Cerebral vasoconstriction after SAH could be an important obstacle in obtaining very good results in aneurysm surgery. Intra-arterial administration of nimodipine is an important and useful treatment, but good results in reversal severe cerebral vasospasm are not always mandatory.